1989
DOI: 10.1182/blood.v73.4.990.bloodjournal734990
|View full text |Cite
|
Sign up to set email alerts
|

Possible effect of secretor locus on plasma concentration of factor VIII and von Willebrand factor

Abstract: A significant fraction (30%) of the genetically determined variance in plasma concentration of the von Willebrand factor antigen (vWf:Ag) has been shown to be related to ABH determinants. Individuals with blood group O, who have the highest amounts of blood group H substance, have the lowest concentration of vWf:Ag. The Lewis substances, Le(a) and Le(b), are biochemically closely related to the ABH substances as both can be produced from the same precursor substance. We studied the effect of the presence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 0 publications
1
30
2
Order By: Relevance
“…51 Furthermore, it has been recently described that the ABO blood group and secretor status have an effect on vWF and factor VIII plasma lev els, thus modifying the blood clotting ability. 62,63 The fact that we found a higher incidence of TRM only in the sub group of minor A and minor AB ABO mismatch is in accordance with other studies, and it is suggested that patients expressing the ABO blood group A antigen are at increased risk of complications after allo PBSCT. 2 A precise explanation for this has not yet been described.…”
Section: Discussionsupporting
confidence: 92%
“…51 Furthermore, it has been recently described that the ABO blood group and secretor status have an effect on vWF and factor VIII plasma lev els, thus modifying the blood clotting ability. 62,63 The fact that we found a higher incidence of TRM only in the sub group of minor A and minor AB ABO mismatch is in accordance with other studies, and it is suggested that patients expressing the ABO blood group A antigen are at increased risk of complications after allo PBSCT. 2 A precise explanation for this has not yet been described.…”
Section: Discussionsupporting
confidence: 92%
“…The ABO, Lewis, and Secretor blood group systems are characterized by the presence or absence of specific terminal carbohydrate determinants on oligosaccharide structures of glycoproteins or glycolipids. Orstavik and coworkers 51 were the first to describe an effect of Secretor blood group on plasma VWF concentration. In a study of 323 twins and 58 blood donors, they found significantly higher VWF:Ag levels in group O individuals with the RBC phenotype Le(a+b-) than in group O individuals with phenotypes Le(a-b+) or Le(a-b-), respectively.…”
Section: Secretor and Lewis Blood Group Systems And Plasma Vwf Levelsmentioning
confidence: 99%
“…Many factors can influence VWF levels including age, stress and hormonal status. The extent of effect on VWF levels attributable to the c.2771G>A allele may be confounded by ABO and other blood groups including Lewis [18] and Secretor [19]. Further loci influencing VWF levels have been sought but await characterization [20].…”
Section: In Vitro Expression Analysis Of Pr924qmentioning
confidence: 99%